Human Rights Perspective of Protection Law for The Outsourcing Bank Workers in Ciptakerja Omnibus Law Bill (Universitas Negeri Semarang, 2022)
In economic development, The bank is one of the economic “spine ”of the country, competition in the world of banking business makes bank needs to focus for creating many products and services which is related to their main competition, for the recruitment staff bank also using outsources company to make easier and everything more efficiency for them. Outsourcing in Indonesia refers to power experts. The Indonesian government also have rights to protects all employee because there are law bills number 13 the year of 2003 (No. 13 Tahun 2003) about outsources employment it said outsources employment could not taking care of the main job in the company but in Omnibus Law bills it is said all the outsources employee could working in everything and all the type of job desk in a company could be handle by outsourcing workers. This journal is using normative method research, this normative method of research it has function is to discuss bills that people talking about. The Author is using a few methods for this journal such as legislative approach, conceptual approach for the main purpose is to help the academic world for having Journal about employment laws.